Determinasi Faktor Biologis, Perilaku, dan Supervisi Terhadap Pengendalian Hipertensi Berbasis Komunitas di Kota Mataram - Rambu Af’Idatussolihah Hayun; Menap; Sismulyanto; Abdul Muin (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aimed to identify key factors influencing the success of hypertension control programs, with a focus on patient compliance and perceptions of program personnel and supervisory performance.A cross-sectional analytical study was conducted involving 80 hypertensive patients from Ampenan and Pejeruk Puskesmas, selected through purposive sampling. Data were collected using structured questionnaires. Chi-square tests were used for bivariate analysis, and binary logistic regression identified the most influential factor. Three variables entered the multivariate model: patient compliance (p = 0.009), perception of program personnel (p = 0.155), and perception of supervisory performance (p = 0.001). Only supervisory performance perception remained statistically significant in the final model (p = 0.001; OR = 5.748; 95% CI = 2.012–16.420), indicating it as the dominant factor even after adjustment for compliance.Supervisory performance strongly influences program success. Strengthening supervision quality and communication within puskesmas is essential to improve patient adherence and the overall effectiveness of hypertension management.